2018
DOI: 10.1177/0165551518811458
|View full text |Cite
|
Sign up to set email alerts
|

Integrating word status for joint detection of sentiment and aspect in reviews

Abstract: A crucial task in sentiment analysis is aspect detection: the step of selecting the aspects on which opinions are expressed. This step anticipates the step of determining whether the opinions on aspects are positive or negative. This article proposes a novel probabilistic generative topic model for aspect-based sentiment analysis which is able to discover the latent structure of a large collection of review documents. The proposed joint sentiment-aspect detection model (SAM) is a generative topic model that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…We evaluate our approach in extraction of multi-word aspects separately. Figure 16 depicts the comparison of our approach to four methods of LRT-based [3], SAM [4], ELDA [8] and MMI-based [14] in extracting three forms of multi- word aspects since the aim of these approaches are extraction multi-word aspects in Persian language from different perspectives. As could be seen, the results of our method outstrip the results of other four approaches in detecting the type C multi-word aspects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluate our approach in extraction of multi-word aspects separately. Figure 16 depicts the comparison of our approach to four methods of LRT-based [3], SAM [4], ELDA [8] and MMI-based [14] in extracting three forms of multi- word aspects since the aim of these approaches are extraction multi-word aspects in Persian language from different perspectives. As could be seen, the results of our method outstrip the results of other four approaches in detecting the type C multi-word aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The author applied SAM on English and Persian languages on three domains of film, cell phone, DVD players' and restaurant reviews. This research listed some obstacles in detecting aspects from Persian sentences as illustrated in table 1 [4].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become a notable vehicle for the fast creation, transmission and discourse of news stories [18][19][20]. Entirely due to the help from Twitter, Web 2.0 has evolved into a much bigger platform for marketing campaigns [21,22], research-work discussion and sentiment analysis [23][24][25][26]. Twitter is used by many research communities as a channel to increase visibility and reach broader audiences that are interested in discussing scientific literature [27,28], and the most Altmetrics Social Media Metrics research has either focused on or included Twitter [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the distribution of sentiments for learners’ focused topics should also be discerned. Previous studies [4 7] have shown that compared with the single topic model latent Dirichlet allocation (LDA), the unified language models of topic and sentiment present more advantages in guiding the generative process of documents such as blogs and reviews. Furthermore, in course forums, textual content is closely associated with their interactive discussion behaviours (e.g.…”
Section: Introductionmentioning
confidence: 99%